OPTIMALISASI PELAYANAN KESEHATAN MELALUI POSTER ALUR POSYANDU INTEGRASI LAYANAN PRIMER: INOVASI PEMBELAJARAN DI WILAYAH KERJA PUSKESMAS NGORESAN - Ubriyanto, Gemintang Antartika; Murti, Bhisma; Fathoni, Afrizal Ikhsanul; Khorudin, Denis; Silamma, Kalvari; Supriadin (CV. Kalimasada Group, 2025)
Background Primary health care services in Indonesia, through Puskesmas and Posyandu, are crucial for improving community health. However, limitations in access and understanding of available services remain significant challenges. Objective This study aims to optimize health services by developing a flowchart poster for the Integrated Primary Health Service (ILP) at Puskesmas Ngoresan. Methodology The methods employed include educating on the service flow using poster media, along with evaluations using pre-tests and post-tests to measure the knowledge and attitudes of the cadres. Results The results indicate that while there were no significant differences in knowledge and attitude scores before and after the intervention, there was an increase in data distribution.Conclusion This activity is expected to enhance the understanding of both cadres and the community regarding health service procedures, as well as encourage active community involvement in health programs. Clear and informative posters serve as effective tools in supporting the cadres' tasks. With the integration of health services, it is anticipated that services will become more efficient and effective, increasing community awareness of the importance of health monitoring.